Pemberdayaan Masyarakat dalam Pencegahan TBC dan Hipertensi Melalui Edukasi dan Inovasi Produk Kesehatan Tradisional - Nisa, Hainun; Marbun, Vermona; Tri Atmodjo Reubun, Yonathan; Ratnah, I; Siregar, Renince; Nuryanti, Lisna; Izwardy, Doddy; Aisyah, Aisyah; Saeful Rahma, Icha; Safira, Bela; Fatimah, Dewi; Aindra, Dinda; Fitriana Febriyanti, Eka; Adi Saputra, Fajar; Rey Safana, Fia; Manda Pika, Indriani; Maknun, Lu luul; Azizah, Nadiyatul; Kamelia, Rika; Apryanti, Selvy; Trilestari, Yulmuhti (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The high prevalence of tuberculosis (TB) and hypertension in Sepanjang Jaya Village, Bekasi, coupled with limited access to health information, prompted the implementation of this community service program. The aim was to improve health literacy, promote the consumption of nutrient-rich local functional foods, and encourage physical activity. A community-based approach was employed, actively involving participants from the initial assessment to implementation and evaluation stages. The activities included: a pre-test and baseline health screening, interactive health education sessions, demonstrations of pumpkin pudding and roselle-ginger tea preparation, group hypertension exercise, a post-test, data analysis, and both formative and summative evaluations. The results indicated a significant improvement in participants’ knowledge scores (from 10–22 to 35–45) and an increase in the proportion of participants with normal blood pressure (from 29% to 69%). However, 74% of participants still exhibited above-normal blood glucose levels. Most participants (92.5%) reported that the program was beneficial and expressed commitment to applying the knowledge gained. In conclusion, participatory community-based health education combined with local functional food utilization proved effective in enhancing health literacy and improving blood pressure control, while sustained support is required for optimal blood glucose management.